Strategi Penerapan Model Pembelajaran Berbasis Audiovisual Untuk Meningkatkan Motivasi dan Hasil Belajar Peserta Didik Kelas V SDN 184/VI Simpang Talang Tembago - Lisa Fitriyah; Aldino Aldino (Master Qualitative Research in Education, 2025)
This study aimed to describe the implementation strategy of an audiovisual-based learning model in improving the motivation and learning outcomes of fifth-grade students at V SDN 184/VI Simpang Talang Tembago Jangkat Timur in the Science and Social Studies (IPAS) subject, particularly on the topic of changes in the states of matter. The research employed a descriptive qualitative approach involving 30 students as research participants. Data were collected through observation, interviews, documentation, and learning outcome tests. The findings revealed that the use of audiovisual media enhanced students’ attention, participation, and learning motivation throughout the instructional process. In addition, there was a significant improvement in students’ learning outcomes, as indicated by the increase in the average score from 60 in the initial stage to 85 after the implementation of audiovisual-based learning, with a learning mastery rate reaching 92%. The study findings indicate that audiovisual media can serve as an effective instructional strategy to help students understand abstract concepts and improve the quality of learning in elementary schools